Prevalence of Familial Hypercholesterolemia in the 1999 to 2012 United States National Health and Nutrition Examination Surveys (NHANES). Issue 11 (15th March 2016) - de Ferranti, Sarah D.; Rodday, Angie Mae; Mendelson, Michael M.; Wong, John B.; Leslie, Laurel K.; Sheldrick, R. Christopher
Abstract : Background—: The prevalence of familial hypercholesterolemia (FH) is commonly reported as 1 in 500. European reports suggest a higher prevalence; the US FH prevalence is unknown. Methods and Results—: The 1999 to 2012 National Health and Nutrition Examination Survey (NHANES) participants ≥20 years of age (n=36 949) were analyzed to estimate the prevalence of FH with available Dutch Lipid Clinic criteria, including low-density lipoprotein cholesterol and personal and family history of premature atherosclerotic cardiovascular disease. Prevalence and confidence intervals of probable/definite FH were calculated for the overall population and by age, sex, obesity status (body mass index ≥30 kg/m 2 ), and race/ethnicity. Results were extrapolated to the 210 million US adults ≥20 years of age. The estimated overall US prevalence of probable/definite FH was 0.40% (95% confidence interval, 0.32–0.48) or 1 in 250 (95% confidence interval, 1 in 311 to 209), suggesting that 834 500 US adults have FH. Prevalence varied by age, being least common in 20 to 29 year olds (0.06%, 1 in 1557) and most common in 60 to 69 year olds (0.85%, 1 in 118). FH prevalence was similar in men and women (0.40%, 1 in 250) but varied by race/ethnicity (whites: 0.40%, 1 in 249; blacks: 0.47%, 1 in 211; Mexican Americans: 0.24%, 1 in 414; other races: 0.29%, 1 in 343). More obese participants qualified as probable/definite FH (0.58%, 1 in 172) than nonobese (0.31%, 1 in 325). Conclusions—: FH, defined with Dutch Lipid Clinic criteria available in NHANES, affects 1 in 250 US adults. Variations in prevalence by age and obesity status suggest that clinical criteria may not be sufficient to estimate FH prevalence.